Perbedaan Perilaku Prososial Berdasarkan Orientasi Peran Jenis - Danny Oscar P; Vivi Gusrini R.Pohan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2006)
Prosocial behaviour emerge based on some factors like situational factor and personal factor, including gender issues. Many researchers who have concern on prosocial behavior in different gender; among others is a study of meta-analyses of college student and senior high school conducted by Eagly and Crowley (1992), showing result that man are more helping than woman consistently. This research is conducted to study further the role of gender orientation in prosocial behavior. This research entangle 200 students in University of North Sumatra which consists of 100 man and 100 woman selected by using technique of incidental sampling. Scale of prosocial tendency relying on the forms of prosocial behavior by Amato (1990) and scale of role of gender orientation pursuant to Bem’s theory (1974) is used to measure the prosocial behavior. Reliability of prosocial tendency scale is equal to 0,962 and role of gender orientation scale is equal to 0,865. Data analyse by one-way ANOVA.Result of data analysis shows that there is difference role of gender orientation among groups of masculine, femininee, androgyny and unclassified in prosocial tendency; with F value = 3,279, probability of p = 0,022. And peculiarly visible difference is between group of androgyny and unclassified group, posed at with probability value equal to 0,018. Result of t-test indicate that there is difference in prosocial tendency between the subject group of man and woman, with F value = 1,888, probability of p equal to 0,014.Keywords: prosocial behavior, role of gender orientation, masculine, feminine, androgyny